RAGE influences obesity in mice: effects of the presence of RAGE on weight gain, AGE accumulation, and insulin levels in mice on a high fat diet - Leuner, Beatrice; Bierhaus, Angelika (Zeitschrift für Gerontologie und Geriatrie, 2012)
Background: The metabolic syndrome is defined by the presence of obesity, insulin resistance, dyslipidemia, and hypertension. Advanced glycation end products (AGEs) are stable end products of the Maillard reaction, whereby AGE accumulation is considered not only a biomarker of aging but is also associated with several degenerative diseases. AGEs are recognized by several receptor molecules of which the receptor of AGEs (RAGE) is currently the most intensively studied receptor. Activation of RAGE causes an unfavorable proinflammatory state and deletion of RAGE in diabetic animals has been reported to protect against atherosclerosis. AGEs and a high fat diet are associated with cardiovascular diseases, whereas is still not clear whether a direct link between high fat nutrition and AGEs exists in vivo. Materials and methods: C57BL/6 and C57BL/6 RAGE −/− mice were fed a high fat diet to induce obesity. Weight, insulin, lipid levels, AGE modifications, and cardiac gene expression were analyzed. Results: The absence of RAGE resulted in accelerated weight gain, increased plasma cholesterol, and higher insulin levels in obese mice. The hearts of normal and obese RAGE −/− mice contained lower levels of the AGE arginine–pyrimidine and 3DG-imidazolone than RAGE + / + animals. RAGE −/− mice also exhibited lower expression of the genes encoding the antioxidative enzymes MnSOD, Cu/ZnSOD, and ceruloplasmin in cardiac tissue, whereas the AGE receptors AGER-1, -2, and -3 were equally expressed in both genotypes. Obese mice of both strains expressed increased amounts of AGER-2. Only obese RAGE + / + mice exhibited a reduced mRNA accumulation of Cu/Zn SOD.Conclusion: These data suggest that RAGE is involved in the development of obesity and insulin resistance.